Carcinoma of endometrium - Aguilar, Ceny (1995)
Carcinoma of endometrium is a malignant tumor derived from endometrial epithelium, due to relative or absolute hyperestronism. According to some authors, it would derive from a series of precursor lesions such as adenomatous hyperplasia. We review 62 cases diagnosed at the Department of Pathology of Daniel A. Carrion Hospital in 24 years of existence. Seventy-five percent reported vaginal bleeding of over one month duration; 68% were puerperal, multiparous or low parity females. Halfof the cases had uterus or increased size, and 30% had normal size uterus. Presumptive clinical diagnisus were dysfunctional uterine bleeding in 32% and cancer in 33%, the latter probably related to previous biopsy and patology report. Eighty percent corresponded to adenocarcinoma and only 6% to the adeno-squamous type. Predominant adenocarcinoma type was endometrioid, with cellular differentiation in 32%. Well differentiated cacinomas were the most frequent. Sixty-four percent did not show infiltartion but to myometrium. Occassional precursor lesions were found.